2014
DOI: 10.1186/2056-5909-20-9
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between nocturnal blood pressure and 24-h urinary sodium excretion in a rural population in Korea

Abstract: Background:The relationship between sodium intake and blood pressure (BP) is affected by many factors such as absolute level of sodium intake, salt sensitivity, and the accuracy or the timing of the BP measurement. There is no epidemiologic study using both ambulatory BP monitoring (ABPM) and 24-h urine sample in a middle-aged general population. Methods: In the rural area, Yeojoo County, Gyunggi Province in South Korea, 218 subjects with age between 30 and 59 years old were measured with ABPM and 24-h urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…To determine the masking effects of an increased BMI, we first investigated the relationship between 24–hour urinary sodium excretion and BP in the total population sample. Consistent with previous studies in this population 4 6 and in other population groups, 29 , 30 we found no relationship. In spite of the inconclusive results in this population, the relationship between sodium level and BP has been well established in a number of studies, 31 34 therefore our current findings require thorough scrutiny.…”
Section: Discussionsupporting
confidence: 90%
“…To determine the masking effects of an increased BMI, we first investigated the relationship between 24–hour urinary sodium excretion and BP in the total population sample. Consistent with previous studies in this population 4 6 and in other population groups, 29 , 30 we found no relationship. In spite of the inconclusive results in this population, the relationship between sodium level and BP has been well established in a number of studies, 31 34 therefore our current findings require thorough scrutiny.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that multiple daily measurements of spot urinary Na/K ratio are strongly related to home hypertension [19]. Previous studies have indicated an association between urinary Na/K ratio and ambulatory BP indices alone [20][21][22]. As these results were derived from different cohorts, it remained unclear, which type of out-of-office BP was remarkably affected by urinary Na/K ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A community-based cross-sectional study in Korea reported that urinary Na/K ratio was positively associated with night-time BP among individuals aged at least 55 years but not among those aged less than 55 years [20]. Another study among 148 Koreans showed that 24-h sodium excretion was an independent factor for night-time BP but not for daytime BP [22]. Meanwhile, a previous study among patients with diabetes in Australia reported that urinary Na/K ratio was not associated with dipping status [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After publication of the article [ 1 ] it was discovered that a citation error had occurred, resulting in different citation numbers in the PDF and HTML files. The correct citation of 20:9 has now been updated in all versions of the manuscript.…”
mentioning
confidence: 99%